Individualitás és választás – útravalók a Whiteheadi folyamat-filozófia megértéséhez - Herth, Ákos (Kultúratudományi Szemle, 2024)
Individuality and decision – Guideposts for understanding the Whiteheadian process philosophy The aim of this paper is to explore the Whiteheadian process philosophy along the lines of individuality and decision. Three aspects of Whitehead's metaphysical system will be explored in this way. The first is Whitehead's individualist conception of Whitehead organized around the subject-superject expression of Process and Reality, according to which reality is based on processes of individualization that presuppose both the subject's self-transcendence and the subject-superject's decision beyond itself. The second aspect introduces a relationalist perspective into the interpretation of reality, according to which individuals do not exist in themselves, their ontological positions being constituted by their relations with others. The third aspect adds an atomic theory to the interpretation: individualization is a pre-temporal, self-creative process of becoming, which is fulfilled in an individual as a reality-creating atomic creature.